Evaluating Communication for Development : a Framework for Social Change. - Lennie, June (Taylor and Francis, 2013)
Evaluating Communication for Development presents a comprehensive framework for evaluating communication for development (C4D). This framework combines the latest thinking from a number of fields in new ways. It critiques dominant instrumental, accountability-based approaches to development and evaluation and offers an alternative holistic, participatory, mixed methods approach based on systems and complexity thinking and other key concepts. It maintains a focus on power, gender and other differences and social norms. The authors have designed the framework as a way to focus on ach.